'I like your new coat': The emergence of secure base and sense of self and other through an art psychotherapy relationship. Issue 2 (3rd April 2017) - Burns, Siobhan; O'Shea, Roseanne
ABSTRACT: Art therapists working with learning disabled clients are used to adapting an art therapy model to work in a way meaningful to the individual. The attuned response to working with past trauma may often be a more interactive responsive style depending on the ability of the client to process cognitive material. This article illustrates in detail an example of an art therapy intervention which demonstrates a flexible, collaborative approach as well as presenting retrospectively gathered evidence of the outcomes of the work. It highlights the ability of an art therapy relationship to enable positive changes in a client whose distressed behaviour could not be managed by behavioural strategies or use of psycho-active medication alone.